Leveraging artificial intelligence in SaaS customer relationship management : A qualitative content analysis of customer stories from CRM system vendors - Sova, Aleksanteri (My University, 2026)
The increased competition resulting from globalisation has led to a need to respond to customer requirements more efficiently. SaaS companies are constantly competing with new market entrants, which has also increased the need for internationalisation. Cloud-based SaaS companies have access to a large amount of customer data, which can be utilised to enhance customer relationship management. The ability to leverage growing customer data significantly determines a company's capacity for effective customer relationship management. By integrating artificial intelligence applications into customer relationship management systems, SaaS companies have the opportunity to accelerate and personalise communication with customers, identify key customers, and optimise their own processes to prevent churn, increase revenue, and succeed in international competition. The potential of AI for SaaS companies is vast, but the variety of ways to utilise it has created a challenge for consistent implementation. At the same time, previous scientific research has become fragmented, focusing on different functionalities and effects of AI, leaving less attention to the differences across various industries in the potential utilisation of AI in customer relationship management. This thesis examines the typical goals and challenges of customer relationship management in SaaS companies, as well as existing AI functionalities as solutions. The literature review consolidates common features related to modern customer relationship management, AI-enhanced functionalities, and key goals and challenges for customer relationship management in SaaS companies. The empirical part of the study was conducted as a qualitative content analysis using secondary, publicly available data. The data consisted of customer stories from seven different companies offering AI-enhanced customer relationship management systems, with SaaS companies as clients. A total of 42 different customer stories were collected, and through analysis, real-world examples of various customer relationship management goals, problems, and AI applications used as solutions were identified. As a result of the study, a theoretical model was developed for the utilisation of AI applications in SaaS companies, including key customer relationship management goals, challenges, and corresponding AI functionalities. Customer relationship management in SaaS companies primarily aims at business growth, which can be achieved by focusing on smaller, more precisely defined operational and strategic objectives. The study indicates that multiple AI functionalities can enhance the realisation of these goals while simultaneously reducing the impact of challenges associated with them. The thesis contributes to academic literature and particularly to the corporate management of SaaS companies. It enhances academic understanding of potential AI applications within the SaaS sector, providing benchmarks for other technologically advanced fields as well. Additionally, the research offers practical insights into how AI can be utilised comprehensively as part of a broader IT strategy. Future research is suggested to explore the effects of different AI functionalities through quantitative methods or qualitatively examine their impact on employees’ or customers’ experiences.

Globalisaation myötä kasvanut kilpailu on johtanut tarpeeseen vastata asiakkaiden toiveisiin entistä tehokkaammin. SaaS-yhtiöt kamppailevat jatkuvasti markkinoille tulevien uusien kilpailijoiden kanssa, mikä on johtanut myös suurempaan kansainvälistymisen tarpeeseen. Pilvipalvelupohjaisilla SaaS-yhtiöillä on käytössään suuri määrä asiakasdataa, jonka avulla asiakkuudenhallintaa voidaan tehostaa. Kyky hyödyntää kasvavaa asiakasdataa määrittääkin suuresti yrityksen kykyä tehokkaaseen asiakkuuksien hallintaan. Integroimalla tekoälysovelluksia asiakkuudenhallintajärjestelmiin SaaS-yhtiöillä on mahdollisuus nopeuttaa ja personoida asiakkaiden kanssa käytävää yhteydenpitoa, tunnistaa tärkeimmät asiakkaat, sekä tehostaa omia prosessejaan poistuman estämiseksi, liikevaihdon kasvattamiseksi sekä kansainvälisessä kilpailussa pärjäämiseksi. Tekoälyn mahdollisuudet SaaS-yhtiöille ovat mittavat, mutta erilaisten hyödyntämisen keinojen määrä on luonut haasteen johdonmukaisen käyttöönoton aloittamiseksi. Samalla aiempi tieteellinen tutkimus on pirstaloitunut keskittyen erilaisiin tekoälyn toiminnallisuuksiin ja vaikutuksiin, jättäen vähemmälle huomiolle erilaisten toimialojen väliset eroavaisuudet tekoälyn mahdollisesta hyödyntämisestä asiakkuudenhallinnassa. Tämä tutkielma tutkii SaaS-yhtiöiden asiakkuusjohtamisen tyypillisiä tavoitteita ja haasteita, sekä näihin ratkaisuna olemassa olevia tekoälytoimintoja. Kirjallisuuskatsauksessa kerätään yhteen tyypillisiä nykypäivän asiakkuusjohtamiseen liittyviä ominaisuuksia, tekoälytehostetun asiakkuusjohtamisen toiminnallisuuksia, sekä SaaS-yhtiöille keskeisiä asiakkuusjohtamisen tavoitteita ja haasteita. Tutkimuksen empiirinen osuus on toteutettu laadullisena sisällönanalyysinä, perustuen toissijaiseen ja julkiseen aineistoon. Aineistoina käytettiin tekoälytehostettuja asiakkuudenhallintajärjestelmiä tarjoavien seitsemän eri yhtiön asiakastarinoita, joissa asiakkaana on SaaS-yhtiö. Tutkimukseen on koottu yhteensä 42 eri asiakastarinaa, joita analysoimalla tunnistettiin tosimaailman esimerkkejä erilaisista asiakkuudenjohtamisen tavoitteista, ongelmista ja ratkaisuna käytetyistä tekoälysovelluksista. Tutkimuksen tuloksena luotiin teoreettinen malli tekoälyn sovellusten hyödyntämiselle SaaS-yhtiöissä, johon sisällytettiin keskeisiä asiakkuudenhallinnan tavoitteita, haasteita, sekä näihin vastaavia tekoälytoiminnallisuuksia. SaaS-yhtiöiden asiakkuudenhallinta pyrkii pääasiassa liiketoiminnalliseen kasvuun, joka voidaan saavuttaa panostamalla pienempiin, tarkemmin määriteltäviin toiminnallisiin ja strategisiin tavoitteisiin. Tutkimuksen myötä voidaan todeta, että tekoälyn usealla erilaisella toiminnallisuudella voidaan tehostaa näiden tavoitteiden toteutumista, samalla vähentäen tavoitetta vastaavien haasteiden vaikutuksia. Tutkielma tuo kontribuutiota akateemiselle kirjallisuudelle sekä erityisesti SaaS-yhtiöiden yritysjohdolle. Tutkimus lisää akateemista ymmärrystä tekoälyn mahdollisista sovelluksista SaaS-toimialalla, tarjoten vertailukohtia myös muille teknologisesti edistyneille aloille. Samalla tutkimus esittää käytännönläheisesti keinoja tekoälyn hyödyntämiselle kokonaisvaltaisella tasolla osana laajempaa IT-strategiaa. Jatkotutkimuksen suunnaksi ehdotetaan erilaisten tekoälytoimintojen vaikutusten tutkimista kvantitatiivisin menetelmin tai laadullisesti tutkimalla erilaisten toimintojen vaikutusta työntekijöiden tai asiakkaiden kokemuksiin.
Keywords: artificial intelligence, AI, customer relationship management, CRM system, international customer relationship management, CRM